Multiple myeloma exosomes establish a favourable bone marrow microenvironment with enhanced angiogenesis and immunosuppression. Issue 2 (7th April 2016) - Wang, Jinheng; De Veirman, Kim; Faict, Sylvia; Frassanito, Maria Antonia; Ribatti, Domenico; Vacca, Angelo; Menu, Eline
Abstract: Multiple myeloma (MM) pathogenesis and progression largely rely on the cells and extracellular factors in the bone marrow (BM) microenvironment. Compelling studies have identified tumour exosomes as key regulators in the maintenance and education of the BM microenvironment by targeting stromal cells, immune cells, and vascular cells. However, the role of MM exosomes in the modification of the BM microenvironment and MM progression remains unclear. Here, we explored the functions of MM exosomes in angiogenesis and immunosuppression in vitro and in vivo . Murine MM exosomes carrying multiple angiogenesis‐related proteins enhanced angiogenesis and directly promoted endothelial cell growth. Several pathways such as signal transducer and activator of transcription 3 (STAT3), c‐Jun N‐terminal kinase, and p53 were modulated by the exosomes in endothelial and BM stromal cells. These exosomes promoted the growth of myeloid‐derived suppressor cells (MDSCs) in naive mice through activation of the STAT3 pathway and changed their subsets to similar phenotypes to those seen in MM‐bearing mice. Moreover, MM exosomes up‐regulated inducible nitric oxide synthase and enhanced the immunosuppressive capacity of BM MDSCs in vivo . Our data show that MM exosomes modulate the BM microenvironment through enhancement of angiogenesis and immunosuppression, which will further facilitate MM progression. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.